ANALISIS KEUNTUNGAN DAN TITIK IMPAS (BREAK EVEN POINT) (Studi Kasus Industri Rumah Tangga Tahu Ibu Sugeng) - Putri Junaini, Adek; Ayuningtyas, Setiani; Akbar, Taufiq (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
The company tries to obtain maximum profit so that the survival of the company continues to run from time to time, good and efficient management is a management that can manage and make decisions that are useful for the survival of the company in order to achieve goals. One approach that management uses in planning earnings is the Break Even Point analysis. Through Break Even Point, a company can easily determine the sales volume needed to achieve the desired profit level. This study aims to analyze the sales of april 2021 to plan profit in May 2021. The type of this research is descriptive quantitative approach, data collection tools using interviews and documentation on home industry Of tofu Ms. Sugeng financial data.